2011
DOI: 10.1111/j.1349-7006.2011.02093.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered humanized anti‐ganglioside GM2 antibody against multiple organ metastasis produced by GM2‐expressing small‐cell lung cancer cells

Abstract: Small-cell lung cancer (SCLC) grows rapidly and metastasizes to multiple organs. We examined the antimetastatic effects of the humanized anti-ganglioside GM2 (GM2) antibodies, BIW-8962 and KM8927, compared with the chimeric antibody KM966, in a SCID mouse model of multiple organ metastases induced by GM2-expressing SCLC cells. BIW-8962 and KM8927 induced higher antibody-dependent cellular cytotoxicity and complement-dependent cytotoxicity than KM966 against the GM2-expressing SCLC cell line SBC-3 in vitro. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…Some tumor cells have altered ganglioside expression compared with untransformed cells, and some overexpress GM2 [56][58]. Humanized antibodies directed against GM2 prevent the formation of organ metastases in mice with small-cell lung cancer [59]. It is possible that ganglioside overexpression in tumor cells alters the susceptibility of certain cancers to reovirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Some tumor cells have altered ganglioside expression compared with untransformed cells, and some overexpress GM2 [56][58]. Humanized antibodies directed against GM2 prevent the formation of organ metastases in mice with small-cell lung cancer [59]. It is possible that ganglioside overexpression in tumor cells alters the susceptibility of certain cancers to reovirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study by Yamada et al provides important evidence supporting both the role of sphingolipids in lung cancer growth and metastasis and the potential for effective therapeutic intervention by targeting sphingolipids. Their study showed high expression of the glycosphingolipid ganglioside GM2 (monosialic ganglioside 2) in small-cell lung cancer (SCLC) human specimens and, using an in vivo tumor xenograft mouse model, demonstrated that an anti-GM2 antibody-based therapy could block SCLC metastases and increase cancer cell apoptosis, thereby prolonging the mouse' survival (Yamada et al 2011). However, as of yet, there are no molecular mechanisms explaining this observation.…”
Section: Sphingolipids In Lung Cancer: a Field That Needs Research mentioning
confidence: 99%
“…ADCC has been described as one of the effector mechanisms associated with antibodies against tumor-associated gangliosides (Chapman et al, 1990;Fukumoto et al, 1999;Terme et al, 2014;Yamada et al, 2011). It was previously reported that high concentrations of mouse 14F7 mAb were required to induce ADCC in GM3(Neu5Gc)-expressing P3 × 63 cells.…”
Section: Discussionmentioning
confidence: 95%